2015
DOI: 10.1021/ac504861d
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Nanoplasmonic Assay To Determine Purity and Titrate Extracellular Vesicles

Abstract: Extracellular Vesicles (EVs) - cell secreted vesicles that carry rich molecular information of the parental cell and constitute an important mode of intercellular communication - are becoming a primary topic in translational medicine. EVs (that comprise exosomes and microvesicles/microparticles) have a size ranging from 40 nm to 1 μm and share several physicochemical proprieties, including size, density, surface charge, and light interaction, with other nano-objects present in body fluids, such as single and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 59 publications
5
90
0
Order By: Relevance
“…The determined AI for the used preparation resulted below 25% of the AI of the dispersed AuNPs (Figure 2A), corresponding to a contaminant content <10 ng/µL (according to the calibration reported in Ref. [9]), that is a high purity preparation. Figure 2B shows the western blot analysis of the EV samples.…”
Section: Extracellular Vesicles Characterizationmentioning
confidence: 86%
See 3 more Smart Citations
“…The determined AI for the used preparation resulted below 25% of the AI of the dispersed AuNPs (Figure 2A), corresponding to a contaminant content <10 ng/µL (according to the calibration reported in Ref. [9]), that is a high purity preparation. Figure 2B shows the western blot analysis of the EV samples.…”
Section: Extracellular Vesicles Characterizationmentioning
confidence: 86%
“…Before further analysis, EV pellets were resuspended in 50 µL PBS 10 mM supplemented with 1:1000 protease inhibitor cocktail. EV preparation purity was graded by a colorimetric nanoplasmonic (CONAN) assay [9], and related UV-vis spectroscopy measurements performed by a EnSight multimode plate reader (Perkin Elmer, Waltham, Massachusetts, United States. EV titration was performed as described in [23]; the calibration line was built with POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, Avanti Polar Lipids, Alabaster, AL, USA) liposomes of about 60 nm size.…”
Section: Extracellular Vesicles Separation and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase both the vesicle yield as well as purity of the isolate, density gradient UC (iodixanol or sucrose) can be used [64,72]. To underscore the superior separation resolution, it was shown that viral particles could be physically separated from EVs by using an iodixanol-based density gradient [73].…”
Section: Ev Purification Protocols and Stabilitymentioning
confidence: 99%